2022
DOI: 10.1111/inm.13097
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID‐19 on the mental health workforce: A rapid review

Abstract: The COVID‐19 pandemic led to significant adaptations to healthcare. Provision of mental healthcare in a changing environment presented healthcare workers with unique challenges and demands, including changes in workload and expectations. To inform current and future healthcare service responses, and adaptations, the current review aimed to collate and examine the impact of the pandemic on mental healthcare workers (MHWs). We conducted a rapid systematic review to examine the overall impact of the COVID‐19 pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 113 publications
(479 reference statements)
0
20
0
Order By: Relevance
“…The COVID-19 Pandemic has been ongoing since 2020, with a significant negative impact on workers' health worldwide, not just limited to physical wellbeing, but also affecting psychological wellbeing (1)(2)(3)(4). COVID-19 has had an impact on occupational health both directly and indirectly.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 Pandemic has been ongoing since 2020, with a significant negative impact on workers' health worldwide, not just limited to physical wellbeing, but also affecting psychological wellbeing (1)(2)(3)(4). COVID-19 has had an impact on occupational health both directly and indirectly.…”
Section: Introductionmentioning
confidence: 99%
“…Understaffing was found to be a pertinent factor that accounted for the turnover intention in the overall sample, and for the rural sub‐sample, but not in the metropolitan sub‐sample. Exacerbated by the COVID‐19 pandemic, understaffing in the public mental health workforce has been cited as a significant public health issue (e.g., Crocker, Gnatt, Haywood, Butterfield, et al, 2023), and one of the most severe workforce shortages in rural Australia is in mental health services (Cosgrave et al, 2018). Interestingly, our metropolitan and rural samples did not significantly differ in their perception of the degree of understaffing, but it was the rural services in which understaffing emerged as contributing to turnover intention.…”
Section: Discussionmentioning
confidence: 99%
“…The challenges faced by the Australian public mental health workforce are further exacerbated by a shortage of qualified candidates applying for advertised positions, the inability to backfill roles after promotions, and the added demands placed on the workforce due to the COVID‐19 pandemic (Crocker, Gnatt, Haywood, Butterfield, et al, 2023; Jiang et al, 2022); these issues have resulted in many services operating with chronic staff shortages (Abeysuriya et al, Hudson & Shen, 2018). In addition to the difficulties in staff retention experienced across the public mental health workforce, generally, rural health services in Australia face additional retention challenges.…”
Section: Introductionmentioning
confidence: 99%
“…However, as we have limited background information regarding possible changes to treatment it is also a possibility that treatments were more spread out, and that children in the transitional group received the same amount of care in a longer period of time as children treated before and entirely during the pandemic. More long-term detrimental effects of COVID-19 on the mental healthcare sector have also been reported, such as persisting increased psychological problems (Alexiou et al, 2021;Crocker et al, 2023;van Doesum et al, 2023) and poorer working conditions (Alexiou et al, 2021;Crocker et al, 2023;Palinkas et al, 2021;Revet et al, 2023;van Doesum et al, 2023) among mental healthcare workers due to the pandemic. Although all three groups achieved similar reductions in internalizing and externalizing problems over time, our findings do suggest that children treated during the pandemic left care with more problems than before the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Restrictions like social distancing and lockdowns also disrupted treatment provision and delivery for children receiving mental health care. As a response to these restrictions the field of mental healthcare experienced a rapid transition to telehealth (Folk et al, 2022; Palinkas et al, 2021; Revet et al, 2023) and mental healthcare workers reported increased psychological problems themselves (Alexiou et al, 2021; Crocker et al, 2023; van Doesum et al, 2023). Mental health professionals also reported overall poorer working conditions as a result of the pandemic (Alexiou et al, 2021; Crocker et al, 2023; Palinkas et al, 2021; Revet et al, 2023; van Doesum et al, 2023).…”
Section: Introductionmentioning
confidence: 99%